Surgical resection versus systemic therapy for breast cancer liver metastases: Results of a European case matched comparison. (May 2018) - Ruiz, A.; van Hillegersberg, R.; Siesling, S.; Castro-Benitez, C.; Sebagh, M.; Wicherts, D.A.; de Ligt, K.M.; Goense, L.; Giacchetti, S.; Castaing, D.; Morère, J.; Adam, R.
Abstract: Background: Resection of breast cancer liver metastases (BCLM) combined with systemic treatment is increasingly accepted but not offered as therapeutic option. New evidence of the additional value of surgery in these patients is scarce while prognoses without surgery remains poor. Patients and methods: For this case matched analysis, all nationally registered patients with BCLM confined to the liver in the Netherlands (systemic group; N = 523) were selected and compared with patients who received systemic treatment and underwent hepatectomy (resection group; N = 139) at a hepatobiliary centre in France. Matching was based on age, decade when diagnosed, interval to metastases, maximum metastases size, single or multiple tumours, chemotherapy, hormonal or targeted therapy after diagnosis. Based on published guidelines, palliative systemic treatment strategies are similar in both European countries. Results: Between 1983 and 2013, 3894 patients were screened for inclusion. Overall median follow-up was 80 months (95% CI 70–90 months). The median, 3- and 5-year overall survival of the whole population was 19 months, 29% and 19%, respectively. The resection and systemic group had median survival of 73 vs. 13 months (P < 0.001), respectively. Three and 5-year survival was 18% and 10% for the systemic group and 75% and 54% for the resection group, respectively. After matching, the resection group had a median overall survival of 82 months with a 3- and 5-year overall survival of 81% and 69%, respectively, compared with a median overall survival of 31 months in the systemic group with a 3- and 5-year overall survival of 32% and 24%, respectively (HR 0.28, 95% CI 0.15–0.52; P < 0.001). Conclusions: For patients with BCLM, liver resection combined with systemic treatment results in improved overall survival compared to systemic treatment alone. Liver resection should be considered in selected cases. Highlights: European comparison of strategies for breast cancer liver metastases. Selected population of liver first and only breast cancer liver metastases, notorious for bad prognosis. Patients who undergo liver resection in addition to systemic treatment live longer. Survival benefit of liver resection remained significant after case matching.